2013
DOI: 10.1007/s00266-012-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Chain Purse-String Suture Used to Shorten the Vertical Incision in Vertical Breast Reduction

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…also published impressive results utilizing a chain purse strain suture technique with vertical breast reduction documenting no elongation of the N-IMF distance over a 12-month follow-up period. 16 All other studies incorporating the vertical reduction pattern reported the elongation of the lower inframammary pole length, bottoming out, or increase in pseudoptosis over the study period. 2 , 6 , 9 , 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…also published impressive results utilizing a chain purse strain suture technique with vertical breast reduction documenting no elongation of the N-IMF distance over a 12-month follow-up period. 16 All other studies incorporating the vertical reduction pattern reported the elongation of the lower inframammary pole length, bottoming out, or increase in pseudoptosis over the study period. 2 , 6 , 9 , 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 98%
“…These include pillar sutures, permanent and absorbable meshes, lipofilling, dermal or dermoglandular slings, autoaugmentation flaps, and muscular slings. 2 , 3 , 4 , 6 , 9 , 11 , 15 , 16 , 17 , 18 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 The meshes used were variable and permanent or partially absorbable meshes generally had better outcomes compared to fully absorbable meshes. Hamdi et al.…”
Section: Discussionmentioning
confidence: 99%